14 - Nekht: Writing the Choice Award Book Titled Multidisciplinary Explorations of Corohysteria Caused by the COVID-2019 Pandemic and Other Achievements by Scholars in the CODESRIA College of Mentors - Abdul Karim Bangura (CODESRIA Bulletin, 2023)